Kinematic Analysis and Optimization Design of 2-CPR/UPU Three Translation Parallel Mechanism - Li Lihong; Zhang Fahai; Zhu Lei (Jixie chuandong)
In view of the real-time control problem caused by the strong coupling of input/output of the parallel mechanism, a three translation parallel mechanism with zero coupling degree is proposed according to the topological design theory and method of parallel mechanism of orientation feature position and orientation characteristic(POC) equation. The mechanism is composed of two CPR and one UPU branch chain, which has the characteristics of analytical position positive solution, low coupling degree, good flexibility of motion and large working space. The main topological characteristics such as azimuth feature set, freedom degree and coupling degree are calculated respectively. The motion constraint equation is established and the analytic expressions of input and output positions of the mechanism are obtained. The conditions of odd shape occurrence are studied, and the performance indexes such as dexterity of reciprocal of Jacobian matrix condition number and operation space at the end of dynamic platform are analyzed. Finally, the global dexterity of the mechanism is taken as the target of configuration optimization and the optimization of size parameters is carried out by the grasshopper optimization algorithm(GOA). It provides theoretical reference for the structural design and high precision position control of the parallel mechanism.